2013
DOI: 10.1016/j.carbon.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron transfer in composite films of reduced graphene oxide and poly(N-methylaniline)

Abstract: Poly(N-methylaniline) (PNMA) has been electropolymerized for the first time from a graphene oxide (GO) dispersion containing 1.0 M HClO 4 . Both GO and perchlorate were incorporated in the PNMA matrix during the electropolymerization resulting in the formation of a mixed composite material of PNMA-ClO 4 and PNMA-GO. Under the acidic polymerization conditions, the carboxylic groups of GO are undissociated and GO is therefore mostly mechanically entrapped in the PNMA matrix while perchlorate functions as the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…5c) comprises open structure/space morphology with graphene flakes embedded within the PV globules, suggesting a graphene interconnection with a polymeric network in the PV-rGO composite assembly. SEM images are similar to those reported for conducting polymers-rGO composites [27,50].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…5c) comprises open structure/space morphology with graphene flakes embedded within the PV globules, suggesting a graphene interconnection with a polymeric network in the PV-rGO composite assembly. SEM images are similar to those reported for conducting polymers-rGO composites [27,50].…”
Section: Resultssupporting
confidence: 84%
“…The composite films however showed highly reversible and a twofold increase in the both cathodic and anodic peak currents compared to GC. The improved redox behavior might be partly due to the bigger electrode surface area but mainly due to the electrochemical reduction of GO to rGO, further increasing the net electrical conductivity and improved electron transfer within the composite films [41,50]. The additional 1/2 h electrochemical reduction of PV-rGO films does not csignificantly improve the electroactivity of PV-rrGO films, once again confirming sufficient reduction of GO during PV-rGO electrodeposition.…”
Section: Resultsmentioning
confidence: 90%
“…[87] Instead of the chemical reduction of GO with reducing agents, such as hydrazine and NaBH 4 , that could cause detrimental effects on the composite structures, electrochemical reduction of GO during the electrochemical polymerization of CPs was found to be an effective approach to highperformance rGO/CP hybrid films. [88,[113][114][115] By using this simple in situ electrochemical reduction strategy, Lindfors and Latonen [88] electropolymerized aniline in a GO solution (pH = 2) to fabricate PANI/rGO flexible hybrid film as supercapacitor electrodes. The as-prepared hybrid film provided an enhancement in conductivity by 30% and capacitance by 15% up to 77 mF cm −2 by the introduction of rGO.…”
Section: Cp/graphene Hybrid Film Supercapacitorsmentioning
confidence: 99%
“…24,55 It was recently shown that the formation of an electrically conducting network of rGO in the poly(N-methylaniline) (PNMA) matrix could be veried by CV measurements with the Ru(NH 3 ) 2+/3+ redox couple. 56 In the potential interval where PNMA is electrically non-conducting (À0.6 to 0.15 V vs. Ag/AgCl/ 3 M KCl), the incorporation of the conducting rGO in the PNMA matrix still provided electron transfer pathways within the PNMA-rGO material and therefore made it possible to detect the redox reaction of the Ru(NH 3 ) 2+/3+ couple in aqueous solution. Hence, to prove the incorporation of graphene or graphite in the PANI matrix, we have performed similar CV measurements in aqueous solutions of 1 mM [Ru(NH 3 ) 6 ]Cl 2 (Ru(II); pH ¼ 9.5), but also in 1 mM K 4 Fe(CN) 6 (Fe(II); pH ¼ 7.8), by cycling the potential between À0.6-0.15 V and À0.2-0.7 V, respectively (Fig.…”
Section: Pani-graphene and Pani-graphite Composite Materialsmentioning
confidence: 99%